A Tour through Graph Theory - Saoub, Karin R (London : Taylor and Francis, 2017)
"A Tour Through Graph Theory introduces graph theory to students who are not mathematics majors. Rather than featuring formal mathematical proofs, the book focuses on explanations and logical reasoning. It also includes thoughtful discussions of historical problems and modern questions. The book inspires readers to learn by working through examples, drawing graphs and exploring concepts. This book distinguishes itself from others covering the same topic. It strikes a balance of focusing on accessible problems for non-mathematical students while providing enough material for a semester-long course. "--Provided by publisher.
Chapter 1 Eulerian Tours -- chapter 2 Hamiltonian Cycles -- chapter 3 Paths -- chapter 4 Trees and Networks -- chapter 5 Matching -- chapter 6 Graph Coloring -- chapter 7 Additional Topics.
OCLC-licensed vendor bibliographic record.
Keywords: Graph theory -- Textbooks